Desarrollo de un plan de mantenimiento productivo total (tpm) en la maquinaria de la empresa “Ffundymec” del cantón Salcedo - Quintana Tenorio, Oscar Manolo (2022)
This thesis work focuses on the development of a total productive maintenance plan TPM that is applied in the company Fundymec of Salcedo Canton and has as its main objective the conservation of systems, elements and components of the equipment involved in the production processes of the plant, for this a survey of information (technical inventory) of the machines installed in the production area in order to know their current status and proceed to develop an analysis of equipment by levels, identifying their technical and functional failures in hierarchical order of each asset. After the application of the TPM plan, work formats are used that describe the technical information used to correctly manage maintenance, among the documents referred to are technical data sheets that contain specific data on the twelve pieces of equipment; The work orders are documents that contain specific instructions of the activities to be performed, spare parts to be used and labor required in the application of the maintenance.